AI in language education: students' perceptions of creating nursery songs with ChatGPT and SunoAI - Prassetyo, Sidarta; Putri, Celya Intan Kharisma (Politeknik Negeri Jember, 2025)
This study explores the use of artificial intelligence (AI) tools, specifically ChatGPT for lyric generation and SunoAI for music composition, in enhancing creativity and language learning within a Media-Assisted Language Learning (MALL) course. While AI’s role in language education is well-studied, its application in creative tasks like nursery song creation has been underexplored. A mixed-methods approach was used, with 48 students participating and data collected from surveys, including quantitative analysis (mean, median, and standard deviation) and qualitative insights from open-ended questions. The study found that participants appreciated both tools for their ease of use, efficiency, and ability to inspire creativity. While there were mixed feelings about the quality of generated lyrics and music, most participants recognized the tools’ value in enhancing their academic and creative projects. The results suggest that AI tools like ChatGPT and SunoAI are effective in supporting language learning and creativity but could benefit from further refinement to improve creative output and user experience. These findings highlight the potential of AI in fostering collaboration and technical skill development, offering valuable implications for future educational applications of AI in creative fields.